Modeling cervical cancer prevention behavior community: a SEM approach - Sulastriningsih, Kursih; Wahyunita, Vina Dwi; Rodiyah, Dedeh (Poltekkes Kemenkes Bandung, 2026)
Background: Cervical cancer is one of the leading causes of death among women and remains a major public health issue, particularly in developing countries such as Indonesia. Objective: This study aimed to analyze the direct and indirect influences, as well as the magnitude of these influences, of the role of midwives, the role of health cadres, family support, and the motivation of women of childbearing age on cervical cancer prevention behavior in the Depok City community. Methods: This research employed a quantitative approach with a cross-sectional design. A total sample of 100 women of childbearing age was selected using a purposive sampling technique. Data were analyzed using Structural Equation Modeling (SEM) with SmartPLS 3.3 and SPSS 24. Results: The findings revealed that cervical cancer prevention behavior was significantly influenced by the role of midwives (29.12%), the role of cadres (18.28%), family support (14.45%), and women’s motivation (27.19%). The direct effect on prevention behavior was 89.0%, while the indirect effect was 1.55%, resulting in a total overall effect of 91%. Conclusion: The role of midwives emerged as the most dominant factor influencing prevention behavior. Increased activeness and competency of midwives in providing education and services contributed to higher participation of women in cervical cancer prevention efforts. These findings are expected to serve as a basis for strengthening promotive and preventive interventions through the empowerment of health workers, families, and communities in supporting healthier behavioral practices.